IMPLEMENTASI FUZZY LOGIC UNTUK SORTASI BUAH TOMAT SECARA OTOMATIS - Sianipar, Agustinus; Handoko, Koko (LPPM Universitas Putera Batam, 2020)
Tomatoes are a type of vegetable that produces fruit. Ripe tomatoes will be bright red witha weight above 80 grams. Tomatoes can be found in the center of traditional shoppingmarkets and wet markets. The traders get tomatoes from farmers in large quantities sothat tomatoes are quite varied. There is a small red, there is a large tomatoes but not yetperfectly ripe and so forth. This is quite troublesome for traders in selling tomatoesbecause they have to be sorted first. To overcome this problem, we need a decisionmaking system to determine the quality of tomatoes and sort them. In this research, thedecision-making system to determine the quality of tomatoes using fuzzy logic Mamdanimethod and sorting tomatoes using Arduino-based conveyer. The result of the researchcan be demonstrated with the MATLAB application and manual count. The MATLAB andmanual results show no difference. The best quality tomatoes are at value 8 with red colorand large size. While the poor quality of tomatoes is at value 2 with green color and largesize. Green tomatoes are certainly not yet ripe and therefor the quality of tomatoes is stillpoor.